Rehabilitation of timber structures – Preparation and environmental service condition effects on the bulk performance of epoxy adhesives - Custódio, J. (2011)
Epoxy adhesives have been used for many years in the rehabilitation of timber structures and are currently the most appropriate adhesive type for on-site operations. However, because they exhibit excellent initial joint strength when tested in standard climate conditions, there has not been a major concern about their service durability. In order to contribute to the ongoing discussion on the reliability of these adhesives, a study was conducted to evaluate the effect of environmental service conditions on the durability of four commercial two-component structural epoxy adhesives, as well as the effect that the type of mixing, curing and postcuring conditions, as well as the presence of moisture have on the adhesives viscoelastic properties. It was found that the preparation conditions, cure schedule and moisture have a significant effect on the performance of the bulk adhesives. Moreover, it was found that under ambient conditions there is potential for under-cure or slow progression of cure for the epoxy adhesive products typically employed in these applications, which in turn can compromise the durability of a bonded joint.